Determinan kemandirian lansia dalam melakukan activity daily living (ADL) - Nadia Fudhiati; Rr. Vita Nurlatif; Dewi Nugraheni (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Elderly individuals 60 years experience physical and cognitive decline that may reduce independence in Activities of Daily Living (ADL). Purpose: To identify factors associated with elderly independence in ADL. Method: A quantitative descriptive study with a cross-sectional design was conducted among 82 elderly respondents. Data were collected using questionnaires and analyzed using chi-square tests and contingency coefficients. Results: Analysis indicates significant relationships between the elderly's level of independence and factors such as age (p=0.003<0.05), gender (p=0.037<0.05), physical health (p=0.000<0.05), social aspects (p=0.015<0.05), economic status (p=0.023<0.05), cognitive function (p=0.014<0.05), and family support (p=0.030<0.05). Conclusion: Elderly independence in ADL is influenced by demographic characteristics, physical health, social and economic factors, cognitive function, and family support. Keywords: ADL; Cognitive Function; Elderly Independence; Family Support. Pendahuluan: Lansia dengan umur 60 tahun mengalami penurunan fungsi fisik dan kognitif yang dapat memengaruhi kemandirian dalam melakukan Activity of Daily Living (ADL). Tujuan: Untuk mengetahui determinan kemandirian lansia dalam melakukan ADL. Metode: Penelitian kuantitatif deskriptif dengan desain cross-sectional dilakukan pada 82 lansia. Data dikumpulkan menggunakan kuesioner dan dianalisis dengan uji chi-square serta koefisien kontingensi. Hasil: Analisis menunjukkan adanya hubungan signifikan antara tingkat kemandirian lansia dengan faktor umur (p=0.003<0.05), jenis kelamin (p=0.037<0.05), kesehatan fisik (p=0.000<0.05), sosial (p=0.015<0.05), ekonomi (p=0.023<0.05), fungsi kognitif (p=0.014<0.05), dan dukungan keluarga (p=0.030<0.05). Simpulan: Kemandirian lansia dipengaruhi oleh faktor demografis, kesehatan, sosial ekonomi, fungsi kognitif, dan dukungan keluarga. Kata Kunci: ADL; Dukungan Keluarga; Fungsi Kognitif; Kemandirian Lansia.